Recent Advances in 4D Bioprinting - Yang, Qingzhen; Gao, Bin; Xu, Feng (Biotechnology journal, 2020)
4D bioprinting has emerged as a powerful technique where the fourth dimension "time" is incorporated with 3D bioprinting. In this technique, the printed bioconstructs are able to change their shapes or functionalities when triggered by either internal or external stimuli. In 4D bioprinting, the materials with/without cells enable the spatial-temporal control of the shape and/or functionality of the constructs. Using this method, researchers have printed bioconstructs that can transform into rather complex structures which are difficult to obtain directly by 3D bioprinting or other methods. Although the history of 4D bioprinting is short, rapid progress in this field is witnessed recently, with focus mainly on developing novel 4D printable materials, exploring novel methods to precisely control the process, and pursuing biomedical applications. To better understand this technique, the recent advances of 4D bioprinting, including the mechanism, structure design principles, applications in biomedical engineering, and also the facing challenges are reviewed.